Morphology of Mixed Langmuir and Langmuir–Schaefer Monolayers with Covered CdSe/CdS/ZnS Quantum Dots and Arachidic Acid - Gorbachev, Ilya A; Smirnov, Andrey V; Glukhovskoy, Evgeny G; Kolesov, Vladimir V; Ivanov, George R; Kuznetsova, Iren E (Langmuir, 2021)
The process of formation of a Langmuir–Schaefer (LS) matrix based on a mixed monolayer of arachidic acid (AA) and 8 nm CdSe/CdS/ZnS quantum dots (QDs) stabilized by molecules of trioctylphosphine oxide (TOPO) was investigated. The change in the morphology, monolayer compressibility, and area per elementary cell of the created mixed monolayers, depending on the ratio of the components, was studied. It is shown that the change in the morphology of Langmuir–Blodgett (LB) monolayers begins to occur at a ratio between the number of QDs and AA molecules of 1:24. Dendrimeric structures with a thickness of the order of 30–40 nm appear in the mixed monolayer when LB film deposition was carried out above the collapse surface pressure of a Langmuir film from only TOPO-covered QDs. Information on the dependence of the morphology of such structures on the molar ratio of the components is necessary for the production of ordered 2D nanostructures containing 0D and 1D objects with quantum bonds. Such nanostructures can be used in nanoelectronic and optoelectronic devices as a sensitive sensor element. The obtained results would be relevant for any type of spherical shape nanoparticles.